Meningkatkan Kemampuan Literasi Dengan Pembiasaan Membaca Cerita Anak Usia 4-5 Tahun - Pinova, Alvina; Maulana, Redi Awal (Pendidikan Guru PAUD Universitas Persatuan Guru Republik Indonesia Semarang, 2025)
The study was conducted based on findings from initial observations, namely that of 16 children, 13, or 87%, still showed low literacy levels. 8 children tended to play alone, 3 children were sleepy, and 2 children felt unsure about what they could do, while the other 3 children had begun to demonstrate good literacy skills. This study was conducted using a Classroom Action Research method with 16 children aged 4-5 years at Cambridge Preschool Child and Care Kindergarten in Depok as subjects. Implementation was carried out using two cycles of action. In the first cycle, literacy increased from 44.01% in the previous cycle and increased by 20.05% to 64.06% in the second cycle. However, due to the results of the first cycle assessment, the researcher conducted a reflection to evaluate the actions of the first cycle and plan steps for the second cycle. For the second cycle, the researcher improved the process of determining agreement between the actions to be carried out in the second cycle, which was very effective in improving children's ability to understand literacy. Cycle I improved outcomes by 19.79%, while cycle II achieved 83.85%.